Pengembangan Sistem Informasi Pemesanan Bahan Baku berbasis Android pada Franchise Qopee - Dwi Retno Ningrum; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Qopee is a beverage product provider that utilizes a franchise business system. Currently the raw material ordering system in the Qopee franchise has been carried out using a web that utilizes the WooCommerce plugin by implementing the Cash On Delivery (COD) payment method. However, the raw material ordering system is less effective and efficient, as is the payment system which is less practical and safe than the non-cash payment system. To solve this problem, an Android-based raw material ordering information system was developed in the Qopee franchise. This system provides features for logging in, logging out, viewing raw material choices, adding raw materials to the shopping cart, selecting payment methods and checkout. The React Native framework was chosen to develop this system on the Android platform by utilizing the WooCommerce Rest API for processing data transactions from the web and Midtrans payment gateway for the payment system. To find out the level of success of the system being developed, a functional test was carried out using the blackbox testing method which obtained valid results on all tests and compatibility tests which resulted in the system being able to run well on all test devices.